2010
DOI: 10.1002/sia.3680
|View full text |Cite
|
Sign up to set email alerts
|

Effect of γ irradiation on the surface properties of wet polysulfone films containing poly(vinylpyrrolidone)

Abstract: In Japan, hemodialyzers are usually sterilized by γ irradiation. However, the polymer materials used in the dialysis membrane, such as polysulfone (PSf) and poly(vinylpyrrolidone) (PVP), undergo crosslinking or degradation on exposure to γ radiation. In the present study, we prepared PSf/PVP films (PVP content, 0-50 wt%) and used atomic force microscopy (AFM) to perform nanoscale evaluations of the effect of γ irradiation (25 and 50 kGy) on the surface properties of wet PSf/PVP surfaces. Force-curve measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 142 publications
0
6
0
Order By: Relevance
“…PSf and PVP are cross-linked when a PSf/PVP film is irradiated by gamma rays [19]. The cross-linked PSf-PVPs are effective in reducing PVP elution from the dialyzers because of high wall shear stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PSf and PVP are cross-linked when a PSf/PVP film is irradiated by gamma rays [19]. The cross-linked PSf-PVPs are effective in reducing PVP elution from the dialyzers because of high wall shear stress.…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated that increasing the PVP content of PSf/PVP surfaces lowered the surface hardness [19]. A PSf material does not swell appreciably when it is wet and forms a hard surface.…”
Section: Changes In Surface Properties Due To Pvp Elutionmentioning
confidence: 98%
“…Steam sterilization or autoclaving can result in a hydrophilic, well-biocompatible dialyzer membrane. 2,13 Gamma irradiation can lead to cross-linking of PVP 16,23 and main polymer as polysulfone, 2,5 which effectively reduce PVP elution from dialyzer membranes 1 or can destruct PVP chains. 10 The influence of the sterilization on PVP amounts eluted from dialyzers investigated here cannot be discussed further, because nonsterile references as well as details of membrane composition (PSu/ PVP, PES/PVP) and sterilization conditions are not accessible.…”
Section: Discussionmentioning
confidence: 99%
“…This led to numerous publications dealing with this topic. 1,[3][4][5][6][7][8][9] Different studies described dependence of PVP elution on methods of sterilization, 1,10,11 aging 3 as well as other conditions. 11 Others focused on investigating the biocompatibility of dialyzers with respect to sterilization 11,12 and further parameters.…”
mentioning
confidence: 99%
See 1 more Smart Citation